'Could do better': Report on the use of special measures in sexual offences cases. (February 2021) - Majeed-Ariss, Rabiya; Brockway, Alice; Cook, Kate; White, Catherine
This article reports on research into the use of 'special measures' in sexual offence cases. It begins by outlining the background: considering the perennial problem of attrition within the criminal justice system; explaining why special measures are considered important; and outlining the rules surrounding their use. The next step is to explain the research and then the discussion turns to the results so far. This study surveyed 61 sexual offence complainants on how they had decided to give evidence in court and what influenced this decision. This is the first time a team has evaluated special measures including the remote live link, from the point of view of the complainants. The complainants' descriptions of their choices were analysed to identify key themes, which are presented here. The results highlight that there are some problems with the practical implementation of these measures, particularly given the views of the complainants.